INTER-ETHNIC TENSION AND ETHNIC CONFLICT: CONTENT, FORMING FACTORS, TYPOLOGY - Sahbanova, M M (History, Archeology and Ethnography of the Caucasus, 2017)
In modern Russian society, there take place the processes of cardinal transformation of socio-economic, political, spiritual and other spheres of its functioning. This fact conditions an urgent need to study risks and threats to preservation of social stability, sustainable development, strengthening of ties and relations in the Russian society. This aspect is especially important in multinational subjects of Russia, which differ in national heterogeneity of the population, degree of socio-economic development of the territories, variability of ethno-cultural norms and value patterns of social life. The article deals with vital and complex issues related to the phenomenon of “interethnic tension” and ethnic conflicts existing in modern national and foreign science, theoretical and methodological approaches to their study, classification criteria, various concepts of the causes and typologies of these phenomena. The author of the article presents classification of interethnic conflicts according to their stages or forms, to the nature of conflicting parties, which makes it possible to single out conflicts of “psychological stereotypes”, “ideological doctrines”, “political institutions”. In the study of the phenomenon of “interethnic tension”, it is important to establish risks and reasons for deterioration of interethnic relations in multinational administrative entities, the role of the factor of ethnic heterogeneity in the emergence of ethnic conflicts in modern Russian society. National diversity is fraught with various negative consequences, risk of interethnic confrontation and ethnic conflicts as polyethnic communities are more at risk of their appearance than mono-national ones.
Keywords: inter-ethnic tension; interethnic relations; interethnic conflict; conflict situation; ethnic groups